Estimating Ad Valorem Equivalents of Non-Tariff Measures Combining Price-Based and Quantity-Based Approaches - Cadot, Olivier (OECD Publishing, 2018)
A novel econometric method is used to estimate trade effects of non-tariff measures (NTMs) for roughly 5 000 traded goods and 80 countries. It explicitly distinguishes several types of measures and ascertains their distinct effects on trade volumes and prices. The latter feature allows disentangling trade-cost effects associated with non-tariff measures from possible demand-enhancing effects that come from reducing information asymmetries and strengthening consumer confidence in imported products. The volume-based estimates yield information on how NTMs ultimately affect trade: the trade cost associated with NTMs, as captured by the ad valorem estimates, often reduces trade volumes, as expected, but not always. In a number of cases, in particular in the sanitary and phytosanitary (SPS) area, trade is found to expand, even though trade costs rise. This is likely explained by closer regulatory environments between the countries examined, but the trade-enhancing features of such measures merit further study
Keywords: Trade